La télévision locale comme outil au service du développement durable: l’expérience Rhizome - Hélène Martin-Brelot (Netcom)
This article identifies the role of a local television regarding sustainable development. Limits are less due to technical barriers than to the capacity of local leaders to recognize the necessity of organising, sharing and diffusing useful information for territorial development.